S132 Survival and pleurodesis outcome in patients with malignant pleural effusion – post-hoc analysis from the TIME-1 trial. (December 2018) - Hassan, M; Mercer, RM; Maskell, N; Pepperell, J; Saba, T; Ali, N; West, A; Miller, RF; Hallifax, RJ; Corcoran, JP; Asciak, R; McCracken, D; et al.
Abstract : Background: Talc pleurodesis is one of the main treatment lines for malignant pleural effusion (MPE). There is data to suggest that survival is better in MPE patients who receive talc pleurodesis in comparison to patients who do not choose to have this treatment. 1 It has been suggested that successful pleurodesis is accompanied by an acute inflammatory response, and this may suggest a possible mechanism of improved survival. 2 This is a post-hoc analysis from the TIME1 trial dataset investigating whether there is difference in survival according to the outcome (i.e. success or not) of pleurodesis. Methods: Data from the TIME 1 RCT was analysed assessing pleurodesis success and survival. Success was defined as no further pleural procedures for up to 3 months post pleurodesis. Patients had undergone either thoracoscopic talc poudrage or talc slurry via chest drain. Results: Data was available for 266 patients, of whom 208 patients (78%) had a successful pleurodesis. The mean age of patients was 72±9 years. The most common malignancies were mesothelioma, lung cancer and breast cancer (25, 22% and 13% respectively). The mean survival time for those with successful pleurodesis was 12 months (95% CI 10.2 to 14 months) months and in those with failed pleurodesis was 7.3 months (95% CI 6–8.6 months). Figure 1 shows the Kaplan-Meier survival curve for the study patients split by pleurodesis outcome (Log rank test: p 0.004). Conclusion: Survival appears to be worse in MPE patients who fail pleurodesis. This might suggest a deleterious biological effect of persistent malignant pleural effusion, differences in stage of disease or an intrapleural inflammatory response leading to enhanced immune response to malignant cells. These findings require further exploration. References: Korsic M, et al. Talc pleurodesis improves survival of patients with malignant pleural effusions: Case-control study. Wien Klin Wochenschr2015;127(23–24):963–969. Mercer R, et al. Does inflammation predict successful pleurodesis? A post hoc analysis from the TIME 1 trial. Thorax2017;72(Suppl 3):A77.2–A78.